Artikel yang berkaitan dengan IT dan matematika di pulau sumba - Ngindi, Yunita Dangu (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
This study aims to describe the plane geometric shapes and identify the ethnomathematical elements embedded in the artistic motifs of the Sumba Cultural House. Ethnomathematics is understood as a bridge connecting mathematical concepts with cultural practices, enabling mathematics to be interpreted in a contextual and meaningful way. This research employed a qualitative descriptive approach. The subject of the study was the Sumba Cultural House located in Kalembu Nga’banga Waitabula, Southwest Sumba Regency, East Nusa Tenggara, Indonesia. Data were collected through direct observation, interviews with key informants, and documentation in the form of photographs and visual recordings. The research instruments consisted of interview and observation guidelines designed to identify geometric elements within the carved motifs.The findings revealed that the motifs of the Sumba Cultural House contain various plane geometric shapes, including triangles, isosceles triangles, equilateral triangles, rhombuses, and circles. These shapes were identified in carvings of women’s jewelry (Mamoli and Maraga), life-path carvings, ornaments of traditional musical instruments, and livestock feeding tool carvings. The geometric patterns, arranged symmetrically and repetitively, indicate the presence of systematic mathematical structures developed through intergenerational cultural practices. These results confirm that the Sumba Cultural House embodies strong ethnomathematical elements and holds significant potential as a contextual resource for mathematics learning. The integration of cultural analysis and mathematical concepts also provides opportunities for developing innovative, culturally based instructional media that align with contemporary educational needs